PEMBUATAN PROGRAM SISTEM INFORMASI PENANGGULANGAN HAMA DAN PENYAKIT TANAMAN BAGI PENYULUH PERTANIAN - jusuf wahyudi; Herlina -; Hesti Nur'aini (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2015)
Extension of plant pests and diseases and tackling has been done by the trainers during the many difficulties and obstacles because of the location and the diversity of the problems faced. The limitations of distance and knowledge of the extension in their duties greatly affect the productivity results. To assist the government in resolving the issue, the need for a computer program information system that can be accessed in the location extension. The program should be able to address various issues of plant pests and diseases as well as mitigation. Program in accordance with the specific needs of course to be built specifically Similarly, in this case the program is made by using the BASIC programming language that has a lot of ability in terms of process automation and published in several editions (versions) according to the development of information of pests and plant diseases as well as mitigation. Techniques used in the preparation of the information systems program using the concept of Waterfalls Sommerville (2001: 45). Methods of data collection related to plant pests and diseases and tackling done by search and literature. The research result obtained is an application program that is easy to administer instructor and has been tested in the presence of pests at random extension. The test results were obtained, that the program has been good and it can be applied but need continued improvement to the development of pest control and plant diseases.Keywords:  hama, penyakit, tanaman, sistem informasi